Metacognition in reading and its relationship with reading proficiency in L1 and L2: An experimental study - Bencke, Diane Blank (2020)
One of the cognitive activities in which metacognition becomes evident is in reading proficiency, by means of metacognitive awareness of reading strategies and the use of metacognitive reading strategies. The aim of this study was (i) to analyze whether there is a relation between metacognition in reading in first language (Portuguese – P) and reading proficiency in L1 (P) or in L2 (English – E), and (ii) whether there is a diverse use of strategies and higher metacognitive consciousness in the groups with higher reading proficiency in L1 and L2. To answer that, an empirical study was developed with 54 university students, divided into four groups according to high and low proficiency reading levels in Portuguese and English. They carried out the following tasks: a self-report task on consciousness of metacognitive reading strategies based on Mokthari and Reichard (2002), Metacognitive Awareness of Reading Strategies Inventory (MARSI), and a task for the assessment of reading comprehension and of the use of strategies using a verbal written retrospective protocol. Correlation was observed between MARSI and strategies in L1 and L2 reading proficiency. This research intends to highlight the importance of the role of metacognitive awareness of reading processes and of the development of reading proficiency in the mother tongue.